Avaliação do qualis-periódicos da medicina III: Análise dos periódicos de anestesiologia e Ginecologia e obstetrícia - Calderon, Iracema de Mattos Paranhos [UNESP] (FapUNIFESP (SciELO), 2015)
Objective: To know the current publication of Anesthesiology and Obstetrics and Gynecology subareas, to support the updating of Qualis Journals criteria in these specific subareas. Method: Cross-sectional, descriptive study in which was evaluated in quantitatively and qualitatively way the bibliographic production of Anesthesiology and Obstetrics and Gynecology subareas, from January 2010 to December 2012. Were investigated the values of the impact factor; calculated (i) the number (n) and the percentage of journals in each stratum Qualis A1, A2, B1, B2, B3, B4 and B5, and (ii) the median values and their extreme limits (minimum values and maximum) and quartiles (p25; p50; p75; p90) of the impact factors in the different strata. Results: The bibliographic production of the three-year period 2010-2012 was published in 69 journals in Anesthesiology subarea and in 345 in Gynecology and Obstetrics. In Anesthesiology, 44% were within the limits of impact factor of superior A1, A2 and B1; in Obstetrics and Gynecology, 42.4% were in those limits and strata. Conclusions: Despite lagging behind by international standards, publications of Anesthesiology and Obstetrics and Gynecology showed tendency to improve the quality. In these sub-areas, the median of journals impact factor is beyond the limits defined by the area in the last assessment. Therefore, it must be reconsidered new indicators to assess this aspect.
Qualis evaluation of medicine III: Analysis of anesthesiology and gynecology and obstetrics journals
Keywords: Impact factor; Indexation; Journal